AEROMYCOLOGICAL STUDIES OF INDOOR ENVIRONMENT OF ADIWASI ASHRAMSHALA,BRAMHAPURI DIST.CHANDRAPUR (MAHARASHTRA) INDIA - ANKUSH L. MISAR; SHANKAR G. KUKREJA; ARVIND J. MUNGOLE (The Bioscan, 2025)
The aim of this study was to determine fungal spore concentration in the indoor environment of Adiwasi ashramshala Bramhapuri dist. Chandrapur (Maharashtra) India and identification of dominant genera. The indoor places having organic substrate occurs more concentration of fungal propagules as compared to the outdoor environment. Meteorological parameters like temperature, humidit , rain fall and the availability of substrate affects fungal spore concentration . In the present study air samples were collected every month fortnightly from February 2023 to January 2024 by exposer Petri plate method and Hi air sampler method to determine monthly and seasonal variation in fungal spore concentration. The dominant genera of fungi found in Adiwasi Ashramshala were Alternaria,Rhizopus, Mucor, Penicillium, Aspergillus, Chaetomium, Cladosporium, Fusarium andCurvularia . Maximum fungal spore concentration was found in the month of August while minimum concentration was in the month May at different sections of sites. Comparatively the concentration of fungal spore varied in accordance with meteorological parameters of every month and availability of substrate at different sections of study area.